Programación y periodización del entrenamiento de fuerza. ¿Qué nos sugieren las últimas investigaciones científicas? - Naclerio Ayllón, Fernando José (KRONOS, 2007)
Scientific research made within the last 40 years has demonstrated how important planning and periodizating is in training to be able to reach the best results in different sports athletes practicing. Strength training, used to improve sports performance and to prevent injuries, is one of the main methodologies used in all kind of sports athletes preparation and, though using different points of view or terminologies (East European, American and American adapted to strength training), in most of the cases research results have demonstrated, with no doubt, that planned strength training increases strength, power or speed and, even, body composition signifi cantly more than non planned one. The proposal of this review is to analyze the most relevant works in this knowledge fi eld, differentiating between the ones focusing in short, medium or long training periods and, at the same time, criticize constructively the last proposals made by main researchers, as well as suggesting useful and easy to use control tools, like effort perception charts.